Speaking Skill through Task Based Learning in English Foreign Language Classroom - Afifah, Nurul; Devana, Trisilia (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
Speaking is one way to express ourselves when communicate. Most of students fail when they perform speaking skill. They faced problems in expressing themselves using in accurate, fluent and even simple sentences. Task based learning is an approach that need the completion of meaningful tasks. Task Based Learning focuses on the use of language for genuine in communication.Â This study used quasi experimental research. The sample of the study is Fourth Semester of English education study program of Baturaja University with the total sample 36 students. The data is conducted of two groups: one experimental group and one control group taught conventionally. Based on the data analysis the researcher concluded that task based learning was effective to improve the studentsâ€™ speaking skill in EFL Classroom. The result data from the mean score of posttest in experimental class was 49,11and the mean score of posttest in control class was 51,88 . While, the value of sig. (2-tailed)=0.000 less than significant level (Î±=0.05), it meant that alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. The researcher concluded the result of posttest in experimental higher than the result of posttest in control class. It means that task based learning was significantly improve the studentsâ€™ speaking skill at fourth semester of English education study program of Baturaja University. Based on the finding on questionnaire, it could be described that almost the students gave positive response on the use of task based learning. The students strongly agree that task based learning help them enjoy in learning English and they also mostly agree that task based activities is a good way to improve English vocabulary.